Analisis Kontestasi Politik Pemilihan Kepala Desa di Desa Drajat Kecamatan Paciran Kabupaten Lamongan Tahun 2022 dalam Perspektif Demokrasi Modern (Studi Kasus di Desa Drajat Kecamatan Paciran Kabupaten Lamongan) - Muchamad Rinaldi; Sutopo, Sutopo (Universitas Sunan Drajat Lamongan, Indonesia, 2023)
Cities and villages have significant differences. Village is an area where the situation and conditions are simpler and homogeneous. The village is the starting point for the development of a government where access to technology has arrived and developed in the village. The opponent of the village is the city. In cities, the situation and conditions are more complex and heterogeneous. The city is a place where the flow of change continues to develop. In order to be more balanced, equity in all fields needs to be increased between villages and cities. This is where the election of the village head is a form of democracy in local government (village) which is said to be considered the most real arena of democracy in the village. In the village head election there is free competition, community participation which is one of the important pillars in the implementation of village head elections and direct elections with the principle of one man one vote where the people can determine who leads through direct elections. This research is included in the field research (Field Research). According to Kartini Kartono, field research is research conducted in real life. Meanwhile, according to Koenjorodininingrat, field research is exploring all social aspects of a certain group or class that is still unknown. Drajat village is a village that can be considered special because in the village there is a guardian's grave, where every day there are pilgrims who come both in the city and in the city. outside the city so that the village of Drajat is also usually called the village of the guardians. In order to organize the village administration and the election of the Drajat village head, the implementation is carried out in accordance with Lamongan Regent Regulation Number 48 of 2021 concerning Simultaneous Village Head Elections in Lamongan Regency.